A novel bispecific antibody targeting CD3 and prolactin receptor (PRLR) against PRLR-expression breast cancer - Yuexian Zhou; Huifang Zong; Lei Han; Yueqing Xie; Hua Jiang; John Gilly; Baohong Zhang; Huili Lu; Jie Chen; Rui Sun; Zhidi Pan; Jianwei Zhu (Journal of Experimental & Clinical Cancer Research, 2020)
Abstract Background Prolactin receptor (PRLR) is highly expressed in a subset of human breast cancer and prostate cancer, which makes it a potential target for cancer treatment. In clinical trials, the blockade of PRLR was shown to be safe but with poor efficacy. It is therefore urgent to develop new therapies against PRLR target. Bispecific antibodies (BsAbs) could guide immune cells toward tumor cells, and produced remarkable effects in some cancers. Methods In this study, a bispecific antibody targeting both tumor antigen PRLR and T cell surface CD3 antigen (PRLR-DbsAb) was constructed by split intein mediated protein transsplicing (BAPTS) system for the first time. Its binding activity was determined by Biacore and Flow cytometry, and target-dependent T cell mediated cytotoxicity was detected using LDH release assay. ELISA was utilized to study the secretion of cytokines by immune cells. Subcutaneous tumor mouse models were used to analyze the in vivo anti-tumor effects of PRLR-DbsAb. Results PRLR-DbsAb in vitro could recruit and activate T cells to promote the release of Th1 cytokines IFN- γ and TNF- α, which could kill PRLR expressed breast cancer cells. In xenograft models with breast cancer cell line T47D, NOD/SCID mice intraperitoneally injected with PRLR-DbsAb exhibited significant inhibition of tumor growth and a longer survival compared to mice treated with PRLR monoclonal antibody (PRLR mAb). Conclusions Both in vitro and in vivo experiments showed PRLR-DbsAb had a potential therapy of cancer treatment potential therapy for cancer. Immunotherapy may be a promising treatment against the tumor target of PRLR.